GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 12810 species occurrences available in GBIF matching the query: TaxonKey: Odocoileus virginianus (Zimmermann, 1780). The dataset includes 12810 records from 122 constituent datasets: 6 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 1 records from Vertebrate Paleontology Division, Yale Peabody Museum. 3 records from Mammal collection of National Museum of Nature and Science. 11 records from HSU Wildlife Mammals. 8 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 1 records from NMMNH Mammal. 4 records from CNMA/Colección de Mamíferos de la Estación de Biología Los Tuxtlas. 6 records from Ohio State University Tetrapod Division - Mammal Collection (OSUM). 3 records from Anymals+plants - Citizen Science Data. 1 records from Mammal collection, Natural History Museum, University of Oslo. 1 records from University of Ghent - Zoology Museum - Vertebratacollectie. 84 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 6 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 114 records from naturgucker. 11 records from Collection Mammalia SMF. 8 records from (UTC) University of Tennessee Mammals Collection. 116 records from TTU Mammals Collection. 100 records from NYSM Mammals. 11 records from Mamíferos de Nuevo León, México (UANL). 77 records from MSB Mammal Collection (Arctos). 13 records from University of California Museum of Paleontology. 1 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 1962 records from Palaeobiology - Vertebrate Fossils Collection - Mammalia - Royal Ontario Museum. 192 records from Field Museum of Natural History (Zoology) Mammal Collection. 141 records from Naturalis Biodiversity Center (NL) - Mammalia. 12 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 1 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 76 records from Paleobiology Database. 62 records from Macaulay Library Audio and Video Collection. 7 records from Mamíferos laguna El Tinije. 5 records from UWYMV Mammal Collection (Arctos). 29 records from New Mexico Biodiversity Collections Consortium database. 3 records from SBMNH Vertebrate Zoology. 10 records from (UTCFM) University of Tennessee - Fossil Mammals Collection. 4 records from Mammal specimens. 1552 records from Mammals Specimens. 8 records from UCM Mammal Collection (Arctos). 28 records from CAS Mammalogy (MAM). 1 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN Fase 1: Estado de México, Hidalgo, San Luis Potosí y Tlaxcala. 10 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 7 records from Colección de mamíferos de la Universidad del Valle. 38 records from NatureServe Network Species Occurrence Data. 10 records from Colección nacional de zoología. 1747 records from iNaturalist research-grade observations. 11 records from Tissues Specimens. 832 records from AMNH Mammal Collections. 3 records from Instituto de ciencias naturales. 4 records from MLZ Mammal Collection (Arctos). 37 records from Cowan Tetrapod Collection - Mammals. 1 records from Queensland Museum provider for OZCAM. 1 records from CCBER Mammalogy Collection. 8 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 30 records from RBINS collections. 2 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 10 records from CHAS Mammalogy. 91 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 103 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 159 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 20 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 34 records from CRCM Vertebrate Collection. 2 records from UAM Mammal Collection (Arctos). 24 records from Computarización de la Colección Nacional de mamíferos del Instituto de Biología, UNAM. 16 records from Geographically tagged INSDC sequences. 11 records from University of Alberta Mammalogy Collection (UAMZ). 14 records from Mammals housed at MHNG, Geneva. 6 records from South Australian Museum Australia provider for OZCAM. 3 records from UMZC Zoological Specimens. 6 records from Computarización de la Colección Regional Durango (Mammalia). 1 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 3 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 15 records from Incorporación de nuevos registros de mamíferos de la región Sierra Norte de Oaxaca. 5 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 31 records from UWBM Mammalogy Collection. 38 records from DMNS Mammal Collection (Arctos). 34 records from LACM Vertebrate Collection. 7 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 522 records from UMMZ Mammal Collection. 492 records from Mammalogy Collection - Royal Ontario Museum. 46 records from CUMV Mammal Collection (Arctos). 1 records from Ditsong Museum. 2 records from Vertebrate specimens of Jyväskylä University Museum. 70 records from Fieldjournal.org observation database. 29 records from USAC Mammals Collection. 2 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 3 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 1 records from Natural History Museum Rotterdam (NL) - Chordata collection. 17 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 31 records from PSM Vertebrates Collection. 273 records from MVZ Mammal Collection (Arctos). 1 records from TTRS Mammals. 61 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 11 records from Natural History Museum (London) Collection Specimens. 3 records from Inventario florístico y faunístico del Parque Nacional Barranca del Cupatitzio, Michoacán. 32 records from Actualización de la base de datos de la colección mastozoológica de El Colegio de la Frontera Sur, San Cristóbal de las Casas. 2 records from Database Schema for UC Davis Wildlife museum. 186 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 180 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 2 records from Bioimages. 25 records from UNSM Vertebrate Specimens. 13 records from Inventario nacional de especies vegetales y animales de uso artesanal. 173 records from LSUMZ Mammals Collection. 92 records from NCSM Mammals Collection. 1 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1443 records from NMNH occurrence DwC-A. 2 records from Colección de Mastozoología. 36 records from Deforestación y fragmentación del hábitat: consecuencias ecológicas sobre la fauna de mamíferos de la selva tropical estacional. 3 records from Colección de Aves y Mamíferos del Valle de Cuatrociénegas, Coah., México (UANL). 45 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 43 records from UAFMC Mammals. 87 records from CNMA/Colección Nacional de mamíferos. 10 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 32 records from FHSM Mammals Collection. 239 records from KUBI Mammalogy Collection. 37 records from UTEP Vertebrates. 12 records from Inventario de los mamíferos de las reservas de la biósfera Mapimí, La Michilía, El Cielo y Calakmul. 4 records from ISU Mammals. 1 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 17 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 455 records from Museum of Comparative Zoology, Harvard University. 6 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_2. 12 records from UCLA Donald R. Dickey Bird and Mammal Collection. 2 records from NCSM Vertebrate Paleontology Collection.
Keywords: GBIF; biodiversity; species occurrences